Insulin indices and metabolic characteristics of young adults with prediabetes: An emerging threat - Ashraf, Koushik; Hasan, Mashfiqul; Bhuiyan, Abdullah Al Noman; Ratul, Rifat Hossain; Sultana, Nusrat; Hasanat, Muhammad Abul (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Prediabetes is often overlooked in young adults, although early insulin resistance and metabolic abnormalities can accelerate the onset of type 2 diabetes. Ethnic and environmental differences necessitate population-specific data to guide preventive strategies. Aims: To compare insulin indices, anthropometric markers, and metabolic profiles between young adults with prediabetes and normoglycemia. Method: This cross-sectional study included 58 participants with prediabetes and 143 with normoglycemia, aged 18–34 years, recruited from the Young Diabetes Clinic at Bangladesh Medical University (September 2023–February 2024). Prediabetes was defined by the ADA OGTT criteria. Anthropometric measurements, lipid profiles, fasting insulin, C-peptide, and insulin indices (HOMA-IR, HOMA-β) were assessed. Statistical comparisons were made between prediabetic and normoglycemic groups. Results: Prediabetes was associated with older age, male sex, and smoking (p<0.05 for all). Obesity was more prevalent in prediabetes, with higher mean BMI (25.9 vs. 23.3 kg/m²), central obesity (72.4% vs. 52.4%), and abnormal waist–height ratio (91.4% vs. 77.6%) in comparison to normoglycemic (p<0.05 for all). Prediabetic participants had higher mean systolic (112 vs. 106 mm Hg) and diastolic (78 vs. 74 mm Hg) blood pressure, increased triglycerides (168 vs. 111 mg/dL), and elevated TG/HDL ratio (4.1 vs. 2.6) (p<0.05 for all). Fasting insulin (18.3 vs. 10.3 μIU/mL) and C-peptide (3.6 vs. 2.3 ng/mL) were significantly higher, with increased HOMA-IR (3.4 vs. 2.1) (p<0.05 for all). However, although reduced in prediabetes, HOMA-β (117 vs. 140) was not significantly different between the two groups. Conclusion: Young Bangladeshi adults with prediabetes demonstrate early-onset obesity, dyslipidemia, hypertension, and insulin resistance, underscoring a trajectory toward type 2 diabetes. Early identification and lifestyle interventions are critical to mitigate this emerging threat. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S50]